MARKET PARTICIPATION DECISION OF SMALLHOLDER FARMERS AND ITS DETERMINANTS IN BANGLADESH - Gani Osmani, Ataul; Hossain, Elias (Economics of Agriculture, 2015)
This paper explores the market participation decision of smallholder farmers in Bangladesh and tries to sort out the most important factors that influence smallholder farmers decision to participate in the output market to sell their produce in Bangladesh. To examine the relationship between the smallholder farmers decision to participate in the market and the factors that affect these farmers decision, a Probit regression model is employed. For this purpose this study uses primary data collected from 100 smallholder farmers of Durgapur Upazila under Rajshahi District. Main findings of this study indicate that there is moderate level of market participation by the households who decide to participate in the market with 57% sales of their produced crops. It is found that farm size, household labour, income from livestock and farm income might be the main factors that affect the smallholder farmers decision to participate in the output market. These findings also suggest that the smallholder farmers would participate more and more in the output market, if farm size, household labour and farm income are increased in one hand and income from livestock is decreased on the other hand. The originality of this paper is that it examines the phenomenon of smallholder farmers commercialization in Bangladesh from the perspectives of market participation, which may create an opportunity for further constructive debate. Finally, development market infrastructure, provision of marketing incentives to smallholder farmers and development of an institutionalized marketing information service are recommended to enhance commercialization of agriculture in Bangladesh.